REGIONAL SPECIALIZATION TRENDS OF LIGHT INDUSTRY IN NAVOI REGION IN THE YEARS OF INDEPENDENCE (American Journal of Research in Humanities and Social Sciences, 2025)
This article analyzes the regional specialization trends of light industry in Navoi region in the period after Uzbekistan gained independence. The article briefly covers the history of the formation of the region and administrative-territorial changes, and determines the role of light industry in the regional economy. The main attention is paid to the specialization trends formed on the basis of the principles of territorial location of enterprises of various branches of light industry (textiles, knitwear, sewing, leather and footwear), proximity to sources of raw materials, the influence of consumer markets and the distribution of labor resources. The article also analyzes the production stages and industry characteristics of light industry enterprises.